Smartphone image-based methods for quick, non-invasive assessments in agriculture - Carreira, Vinicius dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Image processing timely contributes for agricultural purposes. Its outstanding benefit of extracting information from the field can replace timeconsuming, labor-intensive methods. However, most times innovative methods use high-complexity systems and expensive equipment. Low-income regions are not able to finance such costs. Therefore, we concentrate efforts to develop smartphone imagebased methods for agricultural measurements using a mobile device. Smartphone are widespread technology known as flexible, affordable systems. To prove our hypothesis that low-complexity approaches can be useful, we analyzed two agricultural operations. In Chapter 2, we describe how two image-based methods (Region of Interest and Local Maxima) can detect maize plants and estimate their uniformity with overall results of RMSE of 3.98 cm and R² of 0.90. In Chapter 3, we created a smartphone image-based framework to measure macro spray characteristics, including spray angle, distribution shape and solid stream jets. Using image enhancement and morphological operations, our framework accurately resembles traditional methods and can be useful for quick screening of spray nozzles. Therefore, we prove that smartphone use can go beyond ordinary activities and help to spread digital assessments in agriculture.

O processamento de imagens contribui oportunamente para propósitos agrícolas. Seu extraordinário benefício de extrair informações do campo pode substituir métodos demorados e trabalhosos. Entretanto, na maioria das vezes, os métodos inovadores utilizam sistemas de alta complexidade e equipamentos caros. Regiões de baixa renda não são capazes de financiar tais custos. Portanto, concentramos esforços para desenvolver métodos baseados em imagens de smartphone para medições agrícolas. Os smartphones são uma tecnologia difundida conhecida como sistemas flexíveis e acessíveis. Para provar nossa hipótese de que abordagens de baixa complexidade podem ser úteis, analisamos duas operações agrícolas. No Capítulo 2, descrevemos como dois métodos baseados em imagens (Região de Interesse e Máxima Local) podem detectar plantas de milho e estimar sua uniformidade com resultados gerais de RMSE de 3,98 cm e R² de 0,90. No Capítulo 3, criamos uma estrutura baseada em imagem de smartphone para medir as características da pulverização, incluindo ângulo de pulverização, padrão de distribuição e riscos no jato. Usando aprimoramento de imagem e operações morfológicas, nossa estrutura se assemelha com precisão aos métodos tradicionais e pode ser útil para a triagem rápida das pontas de pulverização. Portanto, provamos que o uso do smartphone pode ir além das atividades comuns e ajudar a difundir as avaliações digitais na agricultura.
Métodos baseado em imagens de celular para avaliações rápidas e não invasivas na agricultura
Keywords: Processamento de imagens - Técnicas digitais; Agricultura de precisão; Visão por computador